(3EYQGH GdMOjKs - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s ((3OGQ GdMOjK GdcGedjI s)
(3ChdgG (B:s
(3CeG HYO, aEf LeGYI ef WdHI GdMOjK GdJeShG efj Cf Cedj eNJUQkG aj EYQGH eG jTcd ef GdCdaGX GdhGbYI aj GdCMGOjK s
(3BNQgG (B:s
(3ahGddg dfRd QShd Gddg JbOjQg dbO fRd hgh LhGH GdbSe heKdg bhd GeQF GdbjS BNQg hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B203 - (3U(B315s
(3eQJH Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B46s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B495 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B23 s
Keywords: (3GdfMhs